2006
DOI: 10.1111/j.1741-1130.2006.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Course of Depression in Adoptive and Birth Mothers of Children with Intellectual Disabilities

Abstract: This report extends by an additional 6 years the longitudinal research of Glidden and Schoolcraft, who found that adoptive mothers of children with intellectual disabilities displayed low depression at the initial time of adoption and thereafter, whereas birth mothers reported significantly higher levels when their children were first diagnosed, but not at later times. Depression remained low during the current time of measurement, but mothers who had relatively high depression earlier still reported higher de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…Individual personality traits as well as combinations of traits or profiles can predict many life outcomes including depression and well‐being (Costa & McCrae 1980; Block 1993). In recent years we have reported on the influence that personality of parents rearing children with IDD exerts on depression (Glidden & Schoolcraft 2003; Glidden & Jobe 2006), on parental subjective well‐being (Glidden et al 2006), and parental rewards and worries associated with the child’s transition to adulthood (Jobe & Glidden 2008). For the most part, Neuroticism and Extraversion have had the greatest predictive value, with high levels of Neuroticism associated with poorer adult adjustment outcomes, and high levels of Extraversion associated with better adult adjustment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Individual personality traits as well as combinations of traits or profiles can predict many life outcomes including depression and well‐being (Costa & McCrae 1980; Block 1993). In recent years we have reported on the influence that personality of parents rearing children with IDD exerts on depression (Glidden & Schoolcraft 2003; Glidden & Jobe 2006), on parental subjective well‐being (Glidden et al 2006), and parental rewards and worries associated with the child’s transition to adulthood (Jobe & Glidden 2008). For the most part, Neuroticism and Extraversion have had the greatest predictive value, with high levels of Neuroticism associated with poorer adult adjustment outcomes, and high levels of Extraversion associated with better adult adjustment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, researchers held the belief that there were inevitable and severe negative impacts on parents, including chronic sorrow [Olshansky, 1962]; increased mental and physical health problems [Wolfensberger, 1969;Witt et al, 2003]; increased divorce rates [Gath, 1977]; and elevated levels of psychosocial problems in siblings [Hannah and Midlarsky, 1999]. However, recent meta-analyses and longitudinal studies show that these negative impacts are neither common nor as severe as once thought [Seltzer et al, 2001;Risdall and Singer, 2004;Glidden and Jobe, 2006;Singer, 2006]. Singer [2006] conducted a meta-analysis of 19 comparative studies of depressive symptoms in mothers of children with and without developmental disabilities.…”
mentioning
confidence: 96%
“…Larraine Glidden has done numerous studies with others on the impact of families adopting those with developmental disabilities. Her evidence clearly reveals that those families who chose to welcome a child with a cognitive impairment faired no worse psychologically and emotionally, both for the parents and the fam ily as a whole (Glidden & Jobe, 2006;Glidden, Flaherty, & McGlone, 2000;Glidden, 2000). Studies have also revealed the experience of adopting chil dren as so positive for some that they chose to welcome additional children with intellectual disabilities (Glidden & Johnson, 1999;Goetting & Goetting, 1993).…”
Section: A Potential Strategy For Adopting Children With Down Syndrommentioning
confidence: 86%